2008
DOI: 10.1093/jjco/hyn063
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Pneumonitis Caused by a Migrated Brachytherapy Seed Lodged in the Lung

Abstract: We report a case of radiation pneumonitis caused by a migrated seed lodged in the lung after prostate brachytherapy. A 71-year-old man underwent transperineal interstitial permanent prostate brachytherapy for localized prostate cancer. On the day after brachytherapy, a routine postimplant chest X-ray revealed migration of one seed to the lower lobe of the left lung. After 1 month, pulmonary opacities were observed in the left lower lobe but not near the seed. He was diagnosed with bacterial pneumonia, and anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Most of the embolization events are clinically asymptomatic. Only rarely have reported cases presented with presumed complications related to embolization or radiation-induced soft tissue damage: cardiac arrhythmias from right ventricular migration, acute myocardial infarction from right coronary embolization, and radiation pneumonitis from pulmonary relocation (3,7,12). We do not know if our patients' symptoms are attributable to the seed migration.…”
Section: Discussionmentioning
confidence: 85%
“…Most of the embolization events are clinically asymptomatic. Only rarely have reported cases presented with presumed complications related to embolization or radiation-induced soft tissue damage: cardiac arrhythmias from right ventricular migration, acute myocardial infarction from right coronary embolization, and radiation pneumonitis from pulmonary relocation (3,7,12). We do not know if our patients' symptoms are attributable to the seed migration.…”
Section: Discussionmentioning
confidence: 85%
“…Although it has been reported that most patients with seed migration are asymptomatic, there have been a few reports of seed migration-related sequelae, such as a few anecdotal instances of cardiac arrhythmia, myocardial infarction, and radiation pneumonitis [21,36,37]. Therefore, it is important to try to reduce the incidence of seed migration.…”
Section: Discussionmentioning
confidence: 99%
“…Miura et al reported a case of radiation pneumonitis caused by a single seed migration to the lung after brachytherapy. 10 In the present case, the seed might have been displaced to the bladder wall, persistently affecting the bladder wall. However, we did not find any evidence of seed migration on abdominal X-ray and postplan CT.…”
Section: Discussionmentioning
confidence: 63%